Sequence variation of captive Malayan Gaur (Bos gaurus hubbacki) based on mitochondrial D-loop region DNA sequences - BADRUL MUNIR MD-ZAIN; AQILAH ABDUL-AZIZ; NUR SYAFIKA MOHD-YUSUF; ROSLI NORSYAMIMI; JEFFRINE JAPNING ROVIE-RYAN; KAYAL VIZI KARUPPANNAN; NADIATUR AKMAR ZULKIFLI; SALMAH YAAKOP (Society for Indonesian Biodiversity, 2018)
Md-Zain BM, Abdul-Aziz A, Aifat NR, Mohd-Yusof NS, Norsyamimi R, Rovie-Ryan JJ, Karuppannan KV, Zulkifli NA, Yaakop S. 2018. Sequence variation of captive Malayan Gaur (Bos gaurus hubbacki) based on mitochondrial D-loop region DNA sequences. Biodiversitas 19: 1601-1606. Malayan gaur (Bos gaurus hubbacki) can only be found in Peninsular Malaysia and southern Thailand. The International Union for Conservation of Nature (IUCN) has listed Malayan gaur in the Red List as vulnerable. The main objective of this study was to investigate sequence variation in the mitochondrial D-loop region of B. g. hubbacki from two captive centers. We collected 30 DNA samples of Malayan gaur from Jenderak Selatan Wildlife Conservation Center in Pahang and the Sungkai Wildlife Reserve in Perak. Polymerase chain reactions were performed to amplify all the samples. DNA sequences were analyzed using Neighbor-Joining (NJ) and Maximum Parsimony (MP) methods. Based on the 652 base pairs obtained, we found only seven variable characters with a value of 1% and a genetic distance between the two captive centers of 0.001. Haplotype analyses using DnaSP software detected only four haplotypes between these two captive centers. Both NJ and MP trees portrayed all Malayan gaur individuals in Jenderak Selatan and Sungkai captive centers as belonging to the same clade. Genetic variation of Malayan gaur in these centers is considered low due to individuals possibly sharing the same common parent. This sequence variation information is of paramount importance for the proper breeding and conservation management program of Malayan gaur in the future.